Reducing Sea Turtle Bycatch in the Mediterranean Mixed Demersal Fisheries - Lucchetti, Alessandro; Bargione, Giada; Petetta, Andrea; Vasapollo, Claudio; Virgili, Massimo (Frontiers in Marine Science, 2019)
The sea turtle (Caretta caretta) is the most common sea turtle in the Mediterranean, where incidental catches due to fishing activities are considered the main threat to its conservation. Over 50,000 capture events and likely over 10,000 deaths are estimated to occur in the Italian waters alone. However, current knowledge on the interaction of sea turtles with fishing gears and the implementation of mitigation measures are still poor to hinder the decline of turtle populations in the Mediterranean. In this basin, where fisheries are multispecies, multi-gears and multinational, making demersal fishing activities profitable while preserving sea turtles is a challenge. This study aimed to develop bycatch reducer devices (BRDs) and alternative fishing gears to mitigate the impact of demersal fishing gears on sea turtles: (a) hard and flexible turtle excluder devices (TEDs) were tested in bottom trawling to immediately exclude turtles from the net; (b) visual deterrents (ultraviolet LEDs) were used to illuminate set nets and to alter turtle visual cues, avoiding entanglement during depredation activity. The results showed the different devices did not affect the commercial catch, while bycatch reduction was instead evident. Thus, the study highlights that introducing mitigation measures to reduce sea turtle bycatch in the Mediterranean, where the bycatch of vulnerable species seems as a global issue, can be possible at least in certain areas and periods. Considering fishermen reticence to change the gear traditionally used, determining the optimal gear configuration to minimize commercial loss while reducing bycatch, is the main issue while introducing new technologies. Therefore, a global effort should be done to introduce BRDs in different areas and fisheries of the Mediterranean.